Connecting the Lines between Hypogonadism and Atherosclerosis - Akl C. Fahed; Joanna M. Gholmieh; Sami T. Azar (International Journal of Endocrinology)
Epidemiological studies show that atherosclerotic cardiovascular disease is a leading cause of morbidity and mortality worldwide and point to gender differences with ageing males being at highest risk. Atherosclerosis is a complex process that has several risk factors and mediators. Hypogonadism is a commonly undiagnosed disease that has been associated with many of the events, and risk factors leading to atherosclerosis. The mechanistic relations between testosterone levels, atherosclerotic events, and risk factors are poorly understood in many instances, but the links are clear. In this paper, we summarize the research journey that explains the link between hypogonadism, each of the atherosclerotic events, and risk factors. We look into the different areas from which lessons could be learned, including epidemiological studies, animal and laboratory experiments, studies on androgen deprivation therapy patients, and studies on testosterone-treated patients. We finish by providing recommendations for the clinician and needs for future research.